Genome-Wide Identification of Chalcone Reductase Gene Family in Soybean: Insight into Root-Specific GmCHRs and Phytophthora sojae Resistance - Sepiol, Caroline J.; Yu, Jaeju; Dhaubhadel, Sangeeta (Frontiers in Plant Science, 2017)
Soybean (Glycine max [L.] Merr) is one of the main grain legumes worldwide. Soybean farmers lose billions of dollars’ worth of yield annually due to root and stem rot disease caused by the oomycete Phytophthora sojae. Many strategies have been developed to combat the disease however these methods have proven ineffective in the long term. A more cost effective and durable approach is to select a trait naturally found in soybean that can increase resistance. One such trait is the increased production of phytoalexin glyceollins in soybean. Glyceollins are isoflavonoids, synthesized via the legume-specific branch of general phenylpropanoid pathway. The first key enzyme exclusively involved in glyceollin synthesis is chalcone reductase (CHR) which coacts with chalcone synthase for the production of isoliquirigenin chalcone, the precursor for glyceollin biosynthesis. Here we report the identification of 14 putative CHR genes in soybean where 11 of them are predicted to be functional. Our results show that GmCHRs display tissue-specific gene expression, and that only root-specific GmCHRs are induced upon P. sojae infection. Among 4 root-specific GmCHRs, GmCHR2A is located near a QTL that is linked to P. sojae resistance suggesting GmCHR2A as a novel locus for partial resistance that can be utilized for resistance breeding.